Las tutelas anticipadas de evidencia y urgencia como mecanismo para garantizar la tutela judicial efectiva y el plazo razonable en los proceso de familia en la Provincia de Santa Fe (Papeles, 2021)
The operability of the principles of effective judicial protection and reasonable period and the inclusión of the preventive function within the Argentine system of civil liability requires the building of a preventive, protective and restorative civil justice with the aim of preventing damage or avoid aggravation of damage on individuals rights, especially in family conflicts. In order to comply with the postulates of this protective paradigm it is imperative to provide new legal tools and institutes to the procedural codes able to respond to Citizens demands. Santa Fe Province is in process of passing a new Code of Civil and Commercial Procedure which provides the inclusion of advance guarantees of evidence and urgency in order to establish a justice system swift and efficient.
Keywords: effective judicial protection; reasonable period; preventive function; advance guarantees; civil law